Hubungan TURP Terhadap Kadar Natrium Pasien Benign Prostatic Hyperplasia Di RSI Jemursari Tahun 2022 - 2023 - Prilistyo, Dwimantoro Iman; Masdan Salim, Hotimah; Wibawa, Dayu Satriya; Bhayusakti, Aditya; Alam, Ilham Putra (Bahasa Indonesia, 2024)
Transurethral resection of the prostate (TURP) is a surgical procedure that is the gold standard in treating moderate to severe cases of BPH. Although TURP has been reported as an effective surgical procedure, there are several medical risks that may arise due to TURP procedures. The use of fluid irrigation, a key characteristic of the TURP, can lead to an acute decrease in serum sodium (Na) levels. The conditions of hyponatremia and low plasma osmolarity are directly correlated with the risk of intravascular hemolysis due to increased serum potassium, which then causes hyperkalemia and acidosis. This study aims to examine the serum sodium levels in Benign Prostatic Hyperplasia (BPH) patients undergoing the TURP procedure. This research data is secondary data obtained from medical records at RSI Jemursari in 2022 - 2023. This research was analyzed using a descriptive analytical method to provide an overview of serum sodium levels in BPH patients undergoing the TURP procedure. The results from 20 study samples indicated that the average value of Na levels before TURP was 136.96 mmol/L, while the sodium levels after TURP was 138.02 mmol/L. It was concluded that there was no relationship or difference in sodium levels before and after TURP (p=0.501; 95% CI -4.307 – 2.179).